International labor migration and its impact on national economies - N. Mikhailenko (Управление)
I t is a recognized fact that migration is one of the most important and significant conditions for the successful functioning of the labor market. This article discusses issues related not only to simple migration, but also directly with the international migration of labor. In particular, its impact on the labor supply of national economies has been analyzed, including the impact of labor migration on the formation of the domestic labor market and the total labor potential of society and the state. Directions of interrelation of migration of the population in a key of influence on national economies of the States have been allocated and analyzed.This paper, among other things, provides a classification of modern international migration, identifies five main types of such migration. Studies have been carried out on the dependence and further impact of the type of migration on the domestic economies of States and the international economic situation as a whole. As a result, we consider the positive and negative consequences of labor migration and immigration of the population, as well as their further impact on the reorganization of national economies.The study analyzes the aspects of legislative and legal regulation of migration, including the possibility and basis of such processes in the territory of the Russian Federation. The conclusions drawn up in this article allow us to speak about the impossibility of an unambiguous interpretation of the impact of labor migration on the social and economic indicators of States, since at the same time there are both negative and positive criteria that equally have a direct impact on the categories in the development of international labor migration.